INSTAGRAM AND TELEGRAM ERGONYMS: A STUDY OF NAMING TRENDS AMONG UZBEK YOUTH (Лучшие интеллектуальные исследования, 2025)
This article examines the naming practices (ergonymy) of Uzbek youth on social media platforms, especially Instagram and Telegram. The focus is on how English words and hybrid ergonyms (combinations of English and Uzbek) are used in the branding of online businesses, services, and media accounts. The findings reveal that English borrowings dominate due to their perceived modernity, global appeal, and trustworthiness. These naming choices reflect both individual identity expression and broader cultural shifts toward digital globalization.